Nurses' Perceptions on How Recovery-Oriented Mental Health Care Can Be Developed and Implemented - Kebope Mongie Kealeboga; Mofatiki Eva Manyedi; Salaminah Moloko-Phiri (Hindawi Limited, 2023)
Aim. This study explored how nurses working in inpatient mental health units perceived the development and implementation of a recovery-oriented mental healthcare programme (ROMHCP). Background. The recovery-oriented mental healthcare approach (ROMHCA) in mental health is regarded as the future of mental health services and has been implemented in different countries worldwide. However, regarding developing and implementing the recovery approach, Africa appears to have been left behind by the rest of the continents. Design. The study used a qualitative approach to describe how a recovery-oriented mental healthcare approach could be developed. Methods. Thirty nurses who worked in Botswana's four inpatient mental health facilities consented and voluntarily participated in the study. Data were collected from February to mid-March 2022 through online focus group discussions and analysed using thematic analysis. The COREQ checklist was used to report the findings. Results. Two main themes emerged as follows: (i) developing and implementing a recovery-oriented mental healthcare programme is possible and (ii) certain elements are required to develop and implement ROMHCP. Conclusion. The participants believed that people diagnosed with mental illness could recover from the illness and suggested how it could be achieved. They also contended that the programme's success would lie mainly with multisectoral support from policymakers, facilities, hospital personnel, patients, and the community. Clinical Relevance. ROMHCP has the potential to benefit people with mental illness in the country. In addition, it would allow nurses to improve their knowledge and skills in managing mental illnesses. Patient or Public Contribution. The patients and the general public did not contribute to the study's concept, design, and outcomes. However, the nurses working in mental health facilities volunteered to participate in the study.